Respuesta :

Answer:

x = -10

Step-by-step explanation:

-x + 1 = x + 21

(given)

__________

-x + 1 = x + 21

+x +x

(addition property of equality)

(add the x term on both sides to cancel out -x)

__________

1 = 2x + 21

-21 -21

(subtraction property of equality)

(subtract by 21 on both sides to get rid of the constant term on the x side)

________

-20 = 2x

÷2 ÷2

(division property of equality)

(divide to get rid of the coefficient of 2 in the x term)

_______

-10 = x

(symmetric property of equality)

(switch both sides so that x is on the left)

_______

x = -10

________________________________

Proof by substitution:

x = -10 because

x = -10 → -x + 1 = x + 21 → -(x) + 1 = (x) + 21 → -(-10) + 1 = (-10) + 21 → 10 + 1 = 21 - 10 →

11 = 11

Answer:

x=10

Step-by-step explanation:

Put both of the x on one side, and the numbers on the other side (this breaks down the equation).

This is make it easier for you to add/substract/divide/multiply.